Pengembangan Model Media Pembelajaran untuk Meningkatkan Pemahaman Konsep Teknik Dasar Renang pada Siswa melalui Vitual Reality - Syahril Adam; Zainul Aziz; Andi Ade Surya (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to develop virtual reality-based learning media to improve students' understanding of basic swimming techniques. The research and development method was applied, involving students at State Senior High School 10, East Halmahera. The feasibility test results showed that 80% of respondents gave the developed VR media a "Very Good" rating. Furthermore, the validity and reliability tests of the research instruments demonstrated the validity and consistency of the data. Statistical analysis using the Mann-Whitney test indicated a significant increase in conceptual understanding in the experimental group using VR media, while the control group showed no significant improvement. Therefore, this study concludes that VR learning media is effective in improving conceptual understanding of basic swimming techniques and has the potential to become a relevant innovation in sports learning. Keywords: Learning Media, Conceptual Understanding, Basic Swimming Techniques, Virtual Reality